Effect of plant growth regulators on root development in Coffea arabica L. Rubi seeds grown in vitro - Lacerda, Guilherme Araújo; Chalfun-Júnior, Antonio; Paiva, Luciano Vilela; Melo, Emanuelle Ferreira; Oliveira, Anderson Castro Soares de; Rezende, Juliana Costa de (Coffee Science - ISSN 1984-3909, 1970)
It was evaluated the effect of plant growth regulators in the root development in coffee seeds cv. Rubi (Coffea arabica L. Rubi) grown in vitro. Coffee seeds from adult plants were established on medium MS/2 + sucrose (20 g L-1) + agar (6 g L-1). Four treatments were tested: T1 - control; T2 -BAP (6 mg L-1) + NAA (0,1 mg L-1); T3 -BAP (6 mg L-1); T4 - GA3 (5 mg L-1). The highest rooting response was observed on the control (MS/2 + agar + sucrose). This suggest that rooting can be achieved without the use of plant growth regulators.